Dampak Regulasi Zakat Daerah Terhadap Penguatan Pengelolaan Zakat di Baznas Kota Makassar - Nurfaidah; Muin , Rahmawati; Putra, Trisno Wardy (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
The Zakat Regulation is a rule made by the government concerning the management of zakat with the aim of optimizing management of the zakat in Indonesia. Where fundraising in Indonesia is in Makassar City, there is still a gap between realisation and potential. This investigation aims to find out how the regional regulation of zakat affects the strengthening and collection of funds for zakat in the Basnas of the City of Makassar. The method used in this research is the Qualitative method using a sociological juridical approach. The data source used is primary, i.e. the data obtained directly by the object. (narasumber). As for data obtained through interviews, documentation and observations. The results of this study show that the Regional Zakat Regulation has a positive impact on the collection of Zakat funds in the Basnas of the City of Makassar. Besides, the existence of the Zakat Regulation also has a positive impact on the strengthening of the Basnas of the City of Makassar as a Non-Structural Government Institution.